Effectiveness of Music Therapy on Auditory Hallucination Sensory Perception Disorder at Soerojo Mental Hospital, Magelang - Maemunah, Ai; Purbaningsih, Endah Sari; Fadila, Erida (INDOGENIUS, 2025)
Background & Objective: One of the positive symptoms of schizophrenia is hallucinations. Auditory hallucination is the perception or response of the senses (hearing) to unreal stimuli that influence an individual’s behavior. To determine the effectiveness of music therapy in auditory hallucination sensory perception disorder at Soerojo Mental Hospital, Magelang. Method: Descriptive study with application of previous case study results, using a mental health nursing care approach with the innovation of music therapy as intervention. Result: Music therapy was applied for 3 consecutive days with a 10-minute duration. The problem of sensory perception disorder was resolved, marked by a decrease in verbalization of hearing whispers, hallucinatory behavior, withdrawal, and daydreaming. Conclusion: Music therapy is effective in reducing the level, frequency, and duration of hallucinations in schizophrenic patients.